The Strategy of Developing Weekly Markets into Daily Markets for Archipelago Region as an Effort to Increase Revenue (SWOT Analysis Approach) - Rosida P. Adam; Rustam Abd. Rauf; Suardi Suardi; Husnah Husnah; Suci Rohmawati (Budapest International Research and Critics University, 2022)
This study aims to formulate a strategy for developing the weekly market into a daily market for the archipelago as an effort to increase income. This research method uses a descriptive qualitative research design. Then a SWOT analysis also needs to be carried out to map the strengths, weaknesses, opportunities, and threats. This research was conducted in the Kulingkari, Lebiti, Ketupat, and Kabalutan. Based on the results of the SWOT analysis identification, only Kulingkinari Market and Kabalutan Market are eligible to be developed into daily markets. Then the results of the formulation of the strategy for developing the weekly market into a daily market for the archipelago include: (1) optimizing market development by utilizing the potential and amount of the available Village Budget, (2) providing more adequate land transportation access, (3) increasing market promotion, (4) procurement of waste management systems and provide education to traders and buyers regarding waste management systems, (5) procurement of weather and disaster warning information systems, (6) improve cellular communication network facilities around the Kulingkari market, (7) partnerships between village governments, market managers, traders, and banks or cooperatives, (8) improving the quality of adequate market physical facilities and infrastructure to support market activities.